Caroline Heinrich, Christian Thein: „Das philosophiedidaktische Dreieck in der Diskussion - Albus, Vanessa; Burkard, Anne (Information Philosophie)

Medien im Ethik- und Philosophieunterricht - Albus, Vanessa (Handbuch Medien im Philosophie- und Ethikunterricht)

Texte – Lesen und Verstehen - Albus, Vanessa (Handbuch Medien im Philosophie- und Ethikunterricht)

Lesen im Philosophie- und Ethikunterricht - Albus, Vanessa (ZDPE)

Im Interview mit…. - Albus, Vanessa; Petermann, Hans-Bernhard (ZDPE)

Kristina Peuschel, Anne Burkard (Hrsg.): Sprachliche Bildung und DaZ in den geistes- und gesellschaftlichen Fächern. Tübingen: narr Studienbücher 2019. 259 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Büşra Çakıl: Die Rehabilitierung des Ehrbegriffs. Baden-Baden: Tectum 2018. 210 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Christine Garbe: Lesekompetenz fördern. Stuttgart: Reclam 2020.129 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

“Dear Stranger, This Looks Good on You”: The Effect of Ambiguous Interactive Virtual Presence on Store Loyalty in Offline Retailing - Reimer, T.; Steinhoff, Lena; Leyer, M. (2020 Winter AMA Conference Proceedings, San Diego)

Steuerliche Entlastungsmöglichkeiten für kleine und mittlere Unternehmen wegen der COVID-19-Pandemie - Giese, Henning; Graßl, Benjamin; Holtmann, Svea; Krug, Philipp (Deutsches Steuerrecht)

Die Nutzung digitaler Medien aus der Perspektive der Lehrkräfte - Drossel, Kerstin; Eickelmann, Birgit; Niemann, Jan; Vennemann, Mario (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Sichtweisen von Lehrkräften zum Lernen und Lehren mit digitalen Medien - Niemann, Jan; Eickelmann, Birgit; Drossel, Kerstin (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Lehrerausbildung zum Lernen und Lehren mit digitalen Medien - Drossel, Kerstin; Eickelmann, Birgit; Labusch, Amelie; Niemann, Jan (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, Daniel; Kupfer, Robert; Gude, Maik (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Controversial Histories – Current Views on the Crusades. Engaging the Crusades, Volume Three.

Using Full Duplex Relaying to Reduce Physical Layer Latency in Platooning - Amjad, Muhammad Sohaib; Hardes, Tobias; Schettler, Max; Sommer, Christoph; Dressler, Falko (2019 IEEE Vehicular Networking Conference (VNC))

Towards Heterogeneous Communication Strategies for Urban Platooning at Intersections - Hardes, Tobias; Sommer, Christoph (2019 IEEE Vehicular Networking Conference (VNC))
Platooning promises to solve worldwide traffic problems by using wireless communication for tight control of convoys of vehicles to reduce their inter-vehicle gaps. To date, however, most research on platooning has focused on freeway scenarios. In this paper, we provide a realistic exploration of platooning in urban environments: We consider traffic lights and buildings, realistic vehicle dynamics, platooning controllers, and network communication. We highlight the challenges that urban platooning faces because of the particularities of the Radio Frequency (RF) channel, specifically near the centers of intersections. We demonstrate that using Visible Light Communication (VLC) as an alternative can alleviate some problems, but causes others. Using extensive simulations, we show how a situation-aware combination of VLC and RF communication can be used as a solution: It reduces the overall amount of lost information by approx. 85% compared to traditional approaches.

Das Heilige, die Gewalt und die Liebe in der neuen Kultur des Sichtbaren. Fritz Langs/Thea Harbous "Metropolis" und Bertolt Brechts "Die heilige Johanna der Schlachthöfe" - Morrien, Rita (Weimarer Beiträge)

Neither demarcation nor confrontation. Finding a critical position towards right-wing populism - Haker, Christoph; Otterspeer, Lukas (Zeitschrift für Weiterbildungsforschung)
Abstract Right-wing populism has strongly polarizing effects in politics, education and science—a problem which this article aims to adress. Instead of claiming a demarcation between science and education on the one hand and right-wing populist ideology on the other, we initially focus on continuities. At the same time, we are concerned with finding a critical distance towards right-wing populism. Using the theoretical framework of boundary-work we therefore analyse a case of right-wing populist educational and scientific efforts. Boundary-work can occur in an institutional, content-related and epistemic dimension. While we identify strong continuities in the institutional and content-related dimensions, we see the main difference in the epistemic dimension. In conclusion, we use the results of our analysis to develop a critical position as scientists and educationists towards right-wing populism, drawing consequences for the epistemic, content-related and institutional dimensions.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Right-Wing Populism and Educational Research. Exploring theoretical and methodological perspectives - Haker, Christoph; Otterspeer, Lukas (Zeitschrift für Diskursforschung)